Pengaruh Desain Taman Balai Kota Bandung terhadap Pengguna Ruang Tebuka - Wisnu Saputra; Mulki Alifa Sanafri (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the influence of the design of Bandung City Hall Park on the behavior and experiences of public open space users through an environmental psychology approach. City parks, as public spaces, play a crucial role in supporting social activities, recreation, and the comfort of urban communities. The study employed a qualitative descriptive method with field observations conducted in several key areas of the park, including vegetation, seating areas, pedestrian paths, ponds, and green open spaces. Observations focused on user activity patterns, the intensity of space use, and the forms of social interactions occurring within the park. The results indicate that the physical design of Bandung City Hall Park significantly influences user behavior. Vegetation elements function to create thermal comfort, enhance the visual quality of the environment, and create a calming atmosphere. Seating areas scattered throughout various locations support rest and social interaction, while pedestrian paths facilitate mobility and leisurely walks. The diversity of activities demonstrated that the park functions optimally as a public space that supports relaxation, social interaction, and positive environmental experiences. The research findings confirm that the quality of public open space design is closely related to user behavior, psychological comfort, and the formation of meaning of place for urban residents.